The Impact of the COVID-19 Pandemic on the Offer of Dental Care in the Public Service of a Brazilian Medium-Sized County - Ramirez, Iago; Pereira, Alessandro Aparecido; Ferreira, Eric Batista (ARCHIVES OF HEALTH INVESTIGATION, 2023)
Objective: This study sought to assess the reduction in the offer of dental care by the public service, during the COVID-19 pandemic, in the municipality of Alfenas/MG. Method: Consultation of public data by DATASUS according to a historical series (2015 to 2019) and the pandemic period (2020 to June 2021), which were tabulated and integrated. Descriptive statistics were obtained and application of the Shapiro-Wilk and Wilcoxon-Mann-Whitney statistical tests with 5% significance (p<0.05) were performed. Results: Through two comparisons (historical series and pandemic period; and only 2019 and the pandemic period), there was a significant reduction of procedures offered. Restorative procedures and collective and preventive ones were the most affected with increase in invasive and/or mutilating procedures. It was also noticed a decrease in preventive procedures since 2019 and collective since 2017. Conclusion: The COVID-19 pandemic negatively impacted the offer and type of dental care offered by the public health system in Alfenas/MG.